Iklim Komunikasi Organisasi dalam menumbuhkan Kinerja Guru Madrasah Aliyah Negeri Jakarta Barat - Fauzah Fauzah; Nurhayani Saragih (Syntax Corporation Indonesia, 2024)
This study explains the organizational communication climate in fostering the performance of Madrasah Aliyah Negeri West Jakarta teachers. This descriptive qualitative research uses the paradigm of post positivism. Data was obtained through interviews with 17 informants from 2 schools, 9 from MAN 10, 8 from MAN 12, namely 2 principals, 10 teachers, and 5 students. The Situational Leadership Theory used in this study is supported by the concepts of organization, communication climate and performance. The results of the study show that the organizational communication climate in MAN 10 and MAN 12 West Jakarta is conducive and positive. It is recommended that there be leadership training, encourage openness, collaboration in decision-making, monitoring and evaluation. In overcoming obstacles, it is necessary to have good communication with openness.